2020
DOI: 10.21475/ajcs.20.14.06.p2302
|View full text |Cite
|
Sign up to set email alerts
|

Effect of biochar and inoculation with Trichoderma aureoviride on melon growth and sandy Entisol quality

Abstract: The melon belongs to the family of commercially important cucurbitaceous in the world. However, the production of this crop can be very problematic in some places due to management practices and the climatic instability. Amongst the different options available to overcome these obstacles, the use of biochar often promoted for providing multiple benefits to crops, could contribute in holding more water and nutrients in soil and therefore improve the plant growth. A second way to try to improve the plant develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 18 publications
0
3
0
1
Order By: Relevance
“…In this sense, the soil changes observed and discussed in the present study, whether abiotic or biotic, after applying biochars, envision their potential use as a biofertilizer in the form of an inoculant (De Medeiros et al 2020;França et al 2022). For instance, the management with biochar + Trichoderma species, highlighted by Medeiros et al (2021b), favors the formation of organo-mineral complexes, stimulating edaphic microbial activity (including the increase in microbial communities) and acknowledging this eco-sustainable input as a promising inoculation vehicle, even though the discussion about its viability is still at early stages.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…In this sense, the soil changes observed and discussed in the present study, whether abiotic or biotic, after applying biochars, envision their potential use as a biofertilizer in the form of an inoculant (De Medeiros et al 2020;França et al 2022). For instance, the management with biochar + Trichoderma species, highlighted by Medeiros et al (2021b), favors the formation of organo-mineral complexes, stimulating edaphic microbial activity (including the increase in microbial communities) and acknowledging this eco-sustainable input as a promising inoculation vehicle, even though the discussion about its viability is still at early stages.…”
Section: Discussionmentioning
confidence: 68%
“…Thus, biochar efficiency in managing bacterial diseases refers to its ability to change the soil biota and increase the number of beneficial microorganisms that directly protect plants against the invasion of soil pathogens, such as fungi of the Trichoderma genus (De Medeiros et al 2020), via the production of antibiotics or competition with potentially harmful microorganisms (Elad et al 2010;Akanmu et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Ajeng et al (2020) showed that biochar act to the retention of nutrients to avoid being mathabolized by other phytophatogenic microrganisms or to leaching. This imputs plays an important role in the selective promotion of functional microorganism to dominate the soil microbial community (Liu et al, 2020), promoted root colonization by native arbuscular mycorrhiza and enriches the microbial network (Ajeng et al 2020), as T. aureoviride (Medeiros et al, 2020b).…”
Section: Use Of Biochar As Management Tool Of Plant Diseasesmentioning
confidence: 99%
“…A adição do biocarvão em solos atua na estrutura microbiana, é uma fonte de energia (carbono) e nutrientes (LIMA et al, 2018) que aumentam a abundância e as atividades microbianas através da disponibilidade de carbono (C) lábil (LIU et al, 2020). São recentes e crescentes os estudos acerca deste material, por isso ainda são escassos os conhecimentos a respeito dos seus mecanismos de ação e efeitos sobre a microbiota do solo (ELZOBAIR, et al, 2016;DE MEDEIROS et al, 2020;MEDEIROS et al, 2020) Por outro lado, o biochar tem sido testado como um veículo de inoculação de microorganismos benéficos ao solo e à planta, como é o caso de fungos do gênero Trichoderma (MEDEIROS et al, 2020). Os fungos que compõem esse gênero são amplamente estudados e apresentam diversas aplicações na indústria, meio ambiente e principalmente na agricultura, sendo conhecidos pelos diversos benefícios que oferecem as plantas (CHEN et al, 2020).…”
Section: Introductionunclassified